Caries risk assessment of a sample of children attending preventive specialized dental center in Al Resafa, Baghdad - Muhson, Zaid N; Thabit , Shaymaa; Al-ward , Fatima S; Al Shatari , Sahar AE (Journal of Baghdad College of Dentistry, 2020)
Background: Young children’s oral health maintenance and outcomes are influenced by their parent’s knowledge and beliefs, which affect oral hygiene and healthy eating habits. This study aims at assessing caries risk in children aged 6 months to 6 years attending the Specialized Center of Preventive and Pediatric Dentistry Center at Al-Resafa sector in Baghdad. Materials and Methods: A cross-sectional study was conducted from 15 May – 15 June 2018, all children attended the center (80 children) were assessed by using the standard caries risk assessment tool of the American Academy of Pediatric Dentistry (AAPD). Results: The highest percentage of children was as follows: no fluoride exposure 44(55%), did not brush 46(57.5%), had no special health care needs 77(96.25%), had no missed teeth due to caries 51(63.75%), had no-visible plaque 52(65%), frequent or prolonged between-meal exposure/day 55(68.75%), their mothers had carious lesions in last 7-23 months 34(42.5%); in visual caries: had carious lesions or restorations in last 24 months 67(83.75%), while the incipient carious lesions in last 24 months were 50(62.50%). Most of risk assessment score for the participants was moderate 57(71.3%), followed by low risk 16(20%), while the participants with high risk were 7(8.8%), with a statistically significant association between the risk assessment score and fluoride exposure (p=0.043), sugary foods or drinks(p=0.038), caries experience of the mothers (p=0.001), brushing (p=0.020) visual caries (p=0.000), incipient caries (p= 0.000), missing teeth due to caries (p= 0.001), but no statistical significance with special health care needs (p=0.533) and visible plaque (p=0.259). Conclusion: Moderate-risk of developing dental caries was predominant among the participants, followed by low-risk and less high-risk categories.